Thermal and transport properties of U2PtxIr1–xC2. (24th August 2015) - Kang, Mingu; Wakeham, N; Ni, Ni; Bauer, E D; Kim, Jeehoon; Ronning, F
Abstract: We report thermal and transport properties of U2 Pt x Ir1− x C2 from which a magnetic phase diagram is obtained. Pure U2 IrC2 is an antiferromagnet at 6.5 K, whose Néel temperature initially rises to 13.2 K at x = 0.2 and subsequently is suppressed to zero temperature with increasing Pt content near x = 0.6. Heat capacity divided by temperature at x = 0.6 shows an upturn at low temperature, consistent with the expectations of enhanced quantum fluctuations in the presence of an underlying quantum critical point. The entropy after the phonon contribution has been subtracted has a value of 0.24 R ln2 at the Néel temperature of U2 IrC2, revealing an itinerant nature of the 5  f electrons in this compound. On the Pt rich side of the phase diagram, superconductivity is suppressed by x = 0.85. The residual resistivity increases by a factor of 10 from pure Pt ( x = 1) to x = 0.85 where superconductivity is suppressed to zero. By comparing the phase diagram of Ir doped U2 PtC2 with the phase diagram of pressure tuned and Rh doped U2 PtC2 we demonstrate the role of electronic tuning in this system.